Scrolling for Faith: The Influence of TikTok on Empathy and Islamic Identity Formation - Az-Zahra, Fadya (Icon: Islamic Communication and Contemporary Media Studies, 2025)
This study explores the phenomenon of Scrolling for Faith, where TikTok’s audiovisual format allows short videos to evoke empathy, spiritual reflection, and shifts in religious identity among young Muslim users. Using a qualitative phenomenological approach through interviews and observations, the research identifies three main findings. First, TikTok functions as an emotional and spiritual medium that can trigger religious contemplation through immersive content. Second, the platform serves as a space for identity negotiation, where users express and reshape their Islamic identity both online and offline. Third, TikTok fosters a sense of community and learning, as users feel supported by the Muslim TikTok network and motivated to improve their worship practices and daily habits, while also recognizing the importance of critical awareness to avoid misinformation. The study concludes that TikTok, beyond being a platform of entertainment, plays a significant role in empathy development and the dynamic construction of Islamic identity in the digital era.